ANALISIS KOMPETENSI APARAT PEMERINTAH DESA DALAM MENUNJANG PEMBANGUNAN DESA DI KECAMATAN TELAGA JAYA KABUPATEN GORONTALO - Harsono Ahmad (International Interdisciplinary Conference on Sustainable Development Goals, 2018)
The purpose of this research is to know the capacity building of village government apparatus (study on competency analysis of village government apparatus in supporting the development of the village of Telaga Jaya sub-district, Gorontalo regency). The capacity of village government apparatus is seen from three aspects, namely, coach, self-development and motivation. Besides, the factors inhibit the competence of village government apparatus. The method of research used is descriptive by using the qualitative approach. The research informants were 15 informants. The techniques of collecting data used interview techniques (based on interview guidelines), observation and documentation. Furthermore, data analysis conducted qualitatively. The results of this study indicate that at the level of understanding, the Village Apparatus has not understood the preparation of village development planning. In the skills indicator, the Village Apparatus has performed its duties and functions skillfully. In indicators of ability, Village Apparatus has been able to arrange village development planning in accordance with community expectations and able to manage village funds in accordance with the provisions. This shows that there is an increase in the capacity of the Village Apparatus compared to the previous year. The village apparatus is equipped with training and education that support capacity building